Obesity Following Antiretroviral Therapy (ART) Initiation is Common and Influenced by Both Traditional and HIV-/ART-Specific Risk Factors. (4th October 2017) - Bakal, David; Coelho, Lara; Luz, Paula M; Clark, Jesse L; De Boni, Raquel; Cardoso, Sandra Wagner; Veloso, Valdilea; Lake, Jordan; Grinsztejn, Beatriz
Abstract: Background: Weight gain commonly occurs among HIV-infected (HIV+) adults initiating modern ART regimens, and obesity is increasingly reported in this population. However, data regarding specific risk factors for obesity development after ART initiation are conflicting. Methods: We retrospectively analyzed data from a cohort of HIV+ adults who initiated ART between January 1, 2000 and December 31, 2015 in Rio de Janeiro, Brazil. Body mass index (BMI) was assessed at ART initiation. Participants who were non-obese (BMI < 30kg/m 2 ) at baseline and had ≥90 days of ART exposure were followed for development of obesity. Participants were censored at the time of obesity diagnosis or at end of follow-up (defined as death, loss to follow-up, end of study period or 2 years after their last weight measurement). Incidence rates were estimated using Poisson regression models and risk factor assessment was calculated using Cox regression models accounting for death and loss to follow-up as competing risks. Results: Participants ( n = 1, 794) were 61.3% male, 48.3% white and had a median age of 36.3 years. At ART initiation, participants had a median BMI of 22.6kg/m 2 and BMI category distribution was: underweight 14%, normal weight 56%, overweight 22% and obese 8%. Of the 1, 567 non-obese participants followed after ART initiation, 76% gained weight, 44% increased their BMI category and 18% developed obesity. Median BMI at the end of follow-up was 24.7kg/m 2 (0.4kg/m 2 median annual change), the obesity incidence rate was 37.4 per 1000 person-years and the median time to obesity diagnosis was 1.9 years (vs. 4.7 years of follow-up for participants remaining non-obese). Factors associated with obesity after ART initiation included younger age at ART initiation, female sex, higher baseline BMI, lower baseline CD4 + T lymphocyte count, higher baseline HIV-1 RNA, having an integrase inhibitor as the most-used ART core drug and having diagnoses of hypertension and diabetes mellitus (Figure). Conclusion: Obesity following ART initiation is frequent among HIV+ adults, with rates increasing in recent years. Both traditional (female sex) and HIV-specific (more advanced HIV disease, integrase inhibitor use) risk factors contribute importantly to obesity incidence following ART initiation. Disclosures: All authors: No reported disclosures.